Rhynchophylla total alkaloid rescues autophagy, decreases oxidative stress and improves endothelial vasodilation in spontaneous hypertensive rats - LI Chao; JIANG Feng; LI Yun-lun; JIANG Yue-hua; YANG Wen-qing; SHENG Jie; XU Wen-juan; ZHU Qing-jun (Acta Pharmacologica Sinica, 2018)
Abstract Autophagy plays an important role in alleviating oxidative stress and stabilizing atherosclerotic plaques. However, the potential role of autophagy in endothelial vasodilation function has rarely been studied. This study aimed to investigate whether rhynchophylla total alkaloid (RTA) has a positive role in enhancing autophagy through decreasing oxidative stress, and improving endothelial vasodilation. In oxidized low-density lipoprotein (ox-LDL)-treated human umbilical vein endothelial cells (HUVECs), RTA (200 mg/L) significantly suppressed ox-LDL-induced oxidative stress through rescuing autophagy, and decreased cell apoptosis. In spontaneous hypertensive rats (SHR), administration of RTA (50 mg·kg-1·d-1, ip, for 6 weeks) improved endothelin-dependent vasodilation of thoracic aorta rings. Furthermore, RTA administration significantly increased the antioxidant capacity and alleviated oxidative stress through enhancing autophagy in SHR. In ox-LDL-treated HUVECs, we found that the promotion of autophagy by RTA resulted in activation of the AMPactivated protein kinase (AMPK) signaling pathway. Our results show that RTA treatment rescues the ox-LDL-induced autophagy impairment in HUVECs and improves endothelium-dependent vasodilation function in SHR.